2017
DOI: 10.4081/cp.2017.928
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Fusobacterium necrophorum Liver Abscesses

Abstract: Liver abscesses are an uncommon disease that can present with vague symptoms. Fusobacterium necrophorum causing liver abscesses is a rare condition and only a few cases have been reported. An 88-year-old female presented to her primary care physician with one week of fevers, night sweats, chills, fatigue and vague right upper quadrant abdominal pain. She denied nausea, vomiting, constipation, diarrhea and unintentional weight loss. A computed tomography scan of the abdomen showed two liver abscesses in the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Several studies have identified increased abundances of the oral microbe Fusobacterium in setting of colorectal cancer ( 29 , 33 35 ), liver cirrhosis ( 36 38 ), primary sclerosing cholangitis ( 39 41 ), gastroesophageal reflux disease ( 42 46 ), HIV infection ( 47 49 ), alcoholism ( 50 ), and IBD ( 6 , 10 19 ). Given the prevalence of F. nucleatum in mucosal specimens, we tested the hypothesis that this pathobiont could promote an epithelial proinflammatory response and potentially contribute to intestinal inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have identified increased abundances of the oral microbe Fusobacterium in setting of colorectal cancer ( 29 , 33 35 ), liver cirrhosis ( 36 38 ), primary sclerosing cholangitis ( 39 41 ), gastroesophageal reflux disease ( 42 46 ), HIV infection ( 47 49 ), alcoholism ( 50 ), and IBD ( 6 , 10 19 ). Given the prevalence of F. nucleatum in mucosal specimens, we tested the hypothesis that this pathobiont could promote an epithelial proinflammatory response and potentially contribute to intestinal inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…There are three reported cases of P. micra causing hepatic abscesses and none with a mixture Parvimonas and Fusobacterium [ 3 , 6 14 ]. Our case was similar in presentation with other studies, with chief presenting symptoms of fever, chills, GI upset, and abdominal pain, worsening over a course of several weeks prior to diagnosis [ 6 , 7 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fusobacterium bacteremia is rare, comprising less than 1% of all bacteremia and less than 10% of anaerobic bacteremia [ 1 ]. There are case reports of hepatic abscesses caused by Fusobacterium , most of which are caused by hematogenous spread from either odontogenic infection or inflammation of the GI tract [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a rare cause of liver abscesses and intracerebral infections. F. necrophorum is known for its association with Lemierre’s syndrome, a rare oropharyngeal infectious disease-causing septic thrombophlebitis of the internal jugular vein seen mostly in young immunocompromised patients [ 6 ]. Bacteremia with Fusobacterium spp.…”
Section: Discussionmentioning
confidence: 99%